Odpor k zmene a jeho prekonávanie - Slávik, Štefan (Univerzita Pardubice, 1999)
Managing change is getting to the focus od managerial job. In contemporary enterprise a change is a part of daily working program rather than sustaining a status quo. Capability of observing and accomplishing the attractive changes is unnecessary condition for survival and success in business. Change management dealt with multidimensional and multilayer theme. The paper concentrates on searching the causes of resistence to the change, the posibilities of its reduction and the methods of its overcoming.
Keywords: organizace; pracovníci; změny; Management; psychologie